An unusual case of acute respiratory distress syndrome in a young man - Antonella Cianci; Michele Domenico Spampinato; Benedetta Perna; Giacomo Maroncelli; Chiara Pesci; Roberto De Giorgio; Matteo Guarino (Emergency Care Journal)
Acute Respiratory Distress Syndrome (ARDS) is a complex and progressive lung injury that results in respiratory failure, often caused by pulmonary or systemic disorders. We present a 32-year-old male who developed ARDS following intranasal inhalation of cocaine. Diagnosis was established thorough clinical evaluation, identification of characteristic ultrasonographic patterns, and careful exclusion of other potential causes. The patient was managed with conservative medical therapy, including non-invasive ventilation, bronchodilators, antibiotic therapy, and comprehensive supportive care. Despite initial concerns about the severity of his condition, the patient's outcome was favourable, reflecting the diverse presentations and potential reversibility of ARDS. This case highlights two main aspects: i) the critical role of emergency physicians in recognizing and managing ARDS, even when the underlying cause is not immediately apparent; and ii) the importance of considering illicit drug use as a potential trigger during the initial assessment of respiratory complications.